Mistisisme Muslim Pesisir: Studi atas Ritual Masyarakat Muslim Bajo Sulawesi Tenggara - Abbas Abbas (Institut Agama Islam Negeri Kendari, 2022)
The Bajo people who are identical with marine life have many mantras and rituals as part of mystical behavior that is integrated with their religious life as adherents of the Islamic religion. This study aims to reveal the origins, types and models of mystical behavior of Bajo Muslims in Southeast Sulawesi and identify Islamic values in them. This research is a qualitative descriptive field research with theological-normative, phenomenological, and ethnographic approaches. The subject of this research is the Bajo community in Soropia District, Konawe Regency which is determined by purposive sampling technique by conducting observations and interviews. Data analysis techniques used are domain analysis, taxonomic analysis, comparative analysis and analysis of cultural themes. This study shows that Bajo Muslims in Soropia District are a mix of Bajo people from Salabangka, Central Sulawesi and Bugis from Bajoe-Bone, South Sulawesi, both of which are famous for mystical practices so that the mysticism of Bajo Muslims in Soropia is getting thicker and more varied. Their various mystical behaviors are part of the appreciation for the 'master of the sea', medicine, and taboos/pamali. The value of Islam in their mystical practice is quite strong because almost all of their mantras are filled with religious symbols such as starting with Basmalah and ending with the blessing of 'kunfayakun lailaha illallah' as well as the ritual offering of buffalo heads to the sea which is replaced with thanksgiving in the form of food and fruit. other fruits. The mystical syncretism of Bajo and Islam in Soropia, Southeast Sulawesi is the implication of some residents who have studied at Pesantren al-Khairat in Palu and Pesantren DDI Mangkoso and Kaballangan in South Sulawesi.